Cultural-Based Da’wah Education: A Study toward Totamma’ Tradition in Pambusuang Village Community of Balanipa District of Polewali Mandar Regency: A Study toward Totamma’ Tradition in Pambusuang Village Community of Balanipa District of Polewali Mandar Regency - Moh. Azwar Hairul; Mabrur Mabrur (Farabi, 2022)
This article discusses cultural-based da'wah education against Totamma tradition which develops in the Pambusuang Village, Balanipa District, Polewali Mandar Regency. There are main issues studied that are reviewing the arguments how the tradition is strongly vigorous the relationship between cultural values and religion in the Totamma tradition? and what the meaning of content da'wah education in it?. This article is part of the qualitative research with phenomenological theory of da'wah proposed by Nur Sham became a framework for understanding and analyzing the data. This theory believes that every proselytizing process must be concerned with the purpose internal persuasive and can also be determined by the external persuasive cause. The conclusion of this study refers to three things: First, the tradition of Totamma is an expression of gratitude for children's success in the process of learning to read the Qur'an. Second, the relationship between religious and cultural values in the Totamma tradition is accommodative-theologianistic. The three endeavors to embed mental health and motivation to religious teachings are realized in three things, such as the development of children's qualities, the traditional values provision, and the religious emotional cultivation at an early age. Keywords: Da'wah Education, Culture, Totamma’ Tradition